Video Laryngoscope: To Be or Not (Yet) To Be Used? - Mayang Indah Lestari (Majalah Anestesia & Critical Care, 2021)
In the June/July issue of MACC magazine, an article titled “Comparison of C-MAC® video laryngoscope and Macintosh conventional laryngoscope for nasotracheal intubation convenience in adult Malay race population”, wishes to present to readers, specifically anaesthesiologists, three main points. First, the authors show their outstanding contribution to anaesthesiology research and intensive therapy in Indonesia, particularly regarding airway management. On this occasion, the authors explicitly want to show a comparison of convenience between video laryngoscopes and conventional laryngoscopes in adults, which in reality has not been widely studied.